Análisis de los Ingresos y su Destino del Financiamiento en la Gestión Financiera en el Cuerpo de Bomberos de Guaranda, periodo 2014-2016 - Chimbo Brito, Lida Tannia (2018)
The study sought to perform an analysis of the income and destiny of the financing that the Fire Department handles with the purpose of identifying if it influences or not the financial administration, for which it was necessary to theoretically base everything related to the subject and generate the knowledge necessary to allow the issuance of appropriate conclusions. To gather information, field research was carried out, which allowed to determine the problem and with it the need for this research work since it was possible to determine what by the constant changes in the personnel in charge of the different areas there is a lack of knowledge on the part of the new officers on everything related to income and expenses handled by the Guaranda Canton Fire Department, evidencing the need for a study that seeks to identify sources and destinations of resources; Data collection techniques were applied, such as the survey that reaffirmed the institution's requirement regarding the execution of this project, plus the identification of the main officials in charge of financial administration, destinations of resources, departments to which they are assigned money, after the application of the survey a documentary research was carried out for which it was necessary to access the accounting files as the budget cedulas of income and expenses of the years 2015-2016 of the Fire Department. As part of the research work, the results obtained through the survey, represented in comparative tables per year, of the income and expenses that the institution has maintained in order to identify if the resources are well managed, if considered in the initial allocations, are taken into consideration. they are the adequate ones, and have allowed the adequate development of the organization, finally conclusions and recommendations are generated for the officials in charge of the financial administration of the Fire Department. Keywords: Income, destinations, resources, financial administration, Fire Department. 1